Acute respiratory distress syndrome (ARDS) as an adverse event following immunization: Case definition & guidelines for data collection, analysis, and presentation of immunization safety data. Issue 22 (21st May 2021) - Serazin, Nathan A.; Edem, Bassey; Williams, Sarah R.; Ortiz, Justin R.; Kawade, Anand; Das, Manoj Kumar; Šubelj, Maja; Edwards, Kathryn M.; Parida, Shreemanta K.; Wartel, T. Anh; Munoz, Flor M.; Bastero, Patricia
Abstract: This is a Brighton Collaboration Case Definition of the term "Acute Respiratory Distress Syndrome – ARDS" to be utilized in the evaluation of adverse events following immunization. The Case Definition was developed by a group of experts convened by the Coalition for Epidemic Preparedness Innovations (CEPI) in the context of active development of vaccines for SARS-CoV-2 vaccines and other emerging pathogens. The case definition format of the Brighton Collaboration was followed to develop a consensus definition and defined levels of certainty, after an exhaustive review of the literature and expert consultation. The document underwent peer review by the Brighton Collaboration Network and by selected Expert Reviewers prior to submission. The comments of the reviewers were taken into consideration and edits incorporated in this final manuscript.